Equations

We want to determine whether $x=-1$`x`=−1 is a solution to the equation $\left(x-4\right)^2=25$(`x`−4)2=25, by using substitution.

a

Substitute $x=-1$`x`=−1 into the expression $\left(x-4\right)^2$(`x`−4)2:

b

Is $x=-1$`x`=−1 a solution to the equation $\left(x-4\right)^2=25$(`x`−4)2=25?

No

A

Yes

B

Easy

Approx 2 minutes

Consider the equation $9\left(n+5\right)=4n+50$9(`n`+5)=4`n`+50 for $n=1$`n`=1.

Consider the equation $6a=3a-3$6`a`=3`a`−3 for $a=-1$`a`=−1.

We want to determine whether $x=-1$`x`=−1 is a solution to the equation $\left(x-2\right)^2=9$(`x`−2)2=9, by using substitution.

Sign up to access Practice Questions

Get full access to our content with a Mathspace account

Solve first-degree equations involving one variable, including equations with fractional coefficients